Characterization of amorphous carbon films from 5 nm to 200 nm on single-side polished a-plane sapphire substrates by spectroscopic ellipsometry - Li, Ziqing; Cui, Changcai; Zhou, Xiaolong; Bian, Subiao; Arteaga, Oriol; Xu, Xipeng (Frontiers in Physics, 2022)
In this work, a series of amorphous carbon films were deposited on a-plane sapphire substrates by magnetron sputtering with deposition time from 15 minutes to 8 hours, in order to investigate the thickness and optical properties in the process of growth in a non-destructive way. They were characterized by using Mueller matrix spectroscopic ellipsometry together with topography profilometry and Raman spectroscopy. Two models of a Bruggeman effective medium approximation model and a single Cody-Lorentz oscillator model have been proposed to fit films thickness and optical constants from Ultraviolet (UV) to visible (210 nm-800 nm), and Transmission Electron Microscope (TEM) has been used to verify the proposed model for thickness fitting results. The optical constants of the amorphous carbon film have been determined by fitting together all measurements in samples deposited for 2 hours or more, with the film thickness being the only sample-independent parameter. The results show that the thickness from 5 nm to 200 nm can be characterized in a nondestructive way although there is a relatively large thickness error compared with the TEM results for thin films (d < 20 nm) when the deposition time is less than 2 hours because of the nonuniform deposition in the beginning. The relative error between the TEM and Spectroscopic Ellipsometry (SE) results can be reduced to 1% after 4 hours sample. That means spectroscopic ellipsometry can still provide an indicator for the trend of thickness growth.